A Survey Study of Gastroenterologists' Attitudes and Barriers Toward Therapeutic Drug Monitoring of Anti-TNF Therapy in Inflammatory Bowel Disease. Issue 1 (19th December 2017) - Grossberg, Laurie B; Papamichael, Konstantinos; Feuerstein, Joseph D; Siegel, Corey A; Ullman, Thomas A; Cheifetz, Adam S
Abstract: Background: Therapeutic drug monitoring (TDM) may improve the efficacy and cost-effectiveness of anti-TNF therapy. A standardized approach of utilizing TDM has not been established. The objective of this study was to determine gastroenterologists' attitudes and barriers toward TDM of anti-TNF therapy in clinical practice. Methods: An 18-question survey was distributed to members of the American College of Gastroenterology and Crohn's and Colitis Foundation via email. We collected physician characteristics, practice demographics, and data regarding TDM use and perceived barriers to TDM. Factors associated with the use of TDM were determined by logistic regression analysis. Results: A total of 403 gastroenterologists from 42 US states (76.4% male) met inclusion criteria: 90.1% use TDM, mostly reactively for secondary loss of response (87.1%) and primary nonresponse (66%); 36.6% use TDM proactively. The greatest barriers to TDM implementation were uncertainty about insurance coverage (77.9%), high out-of-pocket patient costs (76.4%), and time lag from serum sample to result (38.5%). Factors independently associated with the use of TDM and proactive TDM were practice in an academic setting ( P = 0.019), and more IBD patients seen per month ( P = 0.015), and Crohn's and Colitis Foundation membership ( P < 0.001), and more IBD patients on anti-TNF therapy per month ( P = 0.006), respectively. If all barriers were removed, an additional one-third of physicians would apply proactive TDM. Conclusions: Lack of insurance coverage, high out-of-pocket costs, and the time lag from test to result limit use of TDM in the United States. Validation of low-cost assays, point of care testing, and studies that standardize the use of TDM are needed to make TDM more commonplace.